Evidence for In Utero Hematogenous Transmission of Group B β-hemolytic Streptococcus - Kathleen Robischon; Marvin S. Amstey (Hindawi Limited, 1994)
Background: The presumed ascending route of group B β-hemolytic streptococcus (GBS) infection from the colonized maternal genital tract is well accepted. This case report proposes a hematogenous, selective infection of one unruptured amniotic sac over the other ruptured amniotic sac in a twin gestation in a patient with known GBS vaginal colonization.